Validation of dental X-ray by cytokine RANTES – comparison of X-ray findings with cytokine overexpression in jawbone - Lechner J (Dove Medical Press, 2014)
Johann Lechner Clinic for Integrative Dentistry, Munich, Germany Introduction: There is a need to clarify the extent to which the most common diagnostic tool in dentistry – two-dimensional panoramic tomography (2D-OPG) – is suitable for identifying fatty degenerative osteolysis of jawbone (FDOJ). Materials and methods: To obtain a qualitative assessment of edentulous jawbone sections, the results from 2D-OPG with a defined X-ray density (XrDn), expression of the cytokine RANTES (regulated on activation, normal T-cell expressed and secreted), and a transalveolar ultrasound system for measuring jawbone density were compared. Results: The difference in the XrDn of healthy jawbone and FDOJ are minimal, whereas RANTES is up to 25-fold higher in FDOJ. In contrast to 2D-OPG, transalveolar ultrasound showed coincidental findings in FDOJ areas. Discussion: Comparisons of the data revealed a discrepancy between the XrDn of 2D-OPGs and the medullary osteopathies in the jawbone like FDOJ. Conclusion: The data suggest that there is a critical attitude toward the use of 2D-OPG as a sole imaging diagnostic tool for assessing chronic inflammatory processes in the jawbone. Specifically, 2D-OPG is objectively not suitable for depicting FDOJ. Keywords: osteonecrotic jawbone, silent inflammation, RANTES, bone density measurement